2019
DOI: 10.1016/j.eats.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Arthroscopic Revision Technique After the Latarjet Procedure

Abstract: The Latarjet procedure is very popular and is the method of choice in cases of glenoid bone loss and anterior-inferior instability or revision procedures. However, recurrence is common after this procedure. One of the methods of revision after the Latarjet procedure is the Eden-Hybinette technique. However, recurrence occurs after this bone grafting procedure as well. The primary reasons for recurrence are graft resorption and capsular deficiency. To improve these outcomes, transfer of the long head of the bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…12 And then Boileau et al applied this fixation method in the Eden-Hybinette procedure for the revision of failed Bristow-Latarjet. 5 Although several studies have shown the advantages of using suture button fixation in the Bristow-Latarjet or Eden-Hybinette procedure, [13][14][15]19,20 there are also studies showing that it might have a higher redislocation rate compared to screw fixation. 21 The main concern about suture button fixation is its inferior biomechanical strength.…”
Section: Discussionmentioning
confidence: 99%
“…12 And then Boileau et al applied this fixation method in the Eden-Hybinette procedure for the revision of failed Bristow-Latarjet. 5 Although several studies have shown the advantages of using suture button fixation in the Bristow-Latarjet or Eden-Hybinette procedure, [13][14][15]19,20 there are also studies showing that it might have a higher redislocation rate compared to screw fixation. 21 The main concern about suture button fixation is its inferior biomechanical strength.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical methods of bony reconstruction for treating recurrent anterior shoulder dislocation include the Latarjet, Bristow, and Eden Hybinette methods, which require open or arthroscopic surgery. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 Exposing the anterior glenoid during open surgery is associated with an increased risk of muscle and nerve damage, affecting patient prognosis. 8 , 9 , 12 , 13 In contrast, arthroscopy allows for clear visualization of the bone block in relation to the glenoid, allowing the bone block to be precisely placed.…”
mentioning
confidence: 99%